Spectrophotmetric Micro determination of promrthazine hydrochloride in pharmaceutical (Baghdad Science Journal, 2005)
a simple accurate and sensitive spectrophotometric method for the determination of promethazine HCI has been developed the method is based on the oxidative coupling reaction of promethazine